The Aesthetics and Meaning of Traditional Paintings: Forbidden Wealth (Pesugihan) by Tjitro Waloejo in Surakarta - Rahmanu Widayat; Mohammad Khizal Mohamed Saat; Sigit Purnomo Adi; Sayid Mataram (Wacana Seni Journal of Arts Discourse, 2020)
At present, Javanese culture is increasingly less powerful in facing the changing times, where art that was once familiar in people’s daily lives has slowly begun to disappear. But Surakarta was fortunate to have Tjitro Waloejo, a traditional painter who died in 1990. He perpetuated the event of collecting illicit wealth (pesugihan) in the form of paintings as a life lesson portraying how some Javanese gathered their wealth under an agreement with Satan. The problem is what the paintings of Tjitro Waloejo are like, and what they really mean. The approach in this study is the concept of “wangun” (beautiful) which the writers explore from Javanese culture to study the art objects (barang kagunan). “Wangun” or beauty of the Javanese becomes (1) the form of “wangun” (beautiful) based on the perspective of the Javanese, (2) the appearance of “ora wangun” (not beautiful) or “aèng” (strange), (3) the form of “wangun” based on the king’s legitimacy or trend, and (4) the forbidden “wangun.” The important findings in the study of “pesugihan” painting reveal that there are perpetuated events of collecting illicit wealth (pesugihan) in the form of paintings as life lessons on how some Javanese gather their wealth under an agreement with demons. It was found that the existence of “wangun” elements and arrangement systems which are classified as forbidden “wangun” (new findings), “angger-angger” (rules), and “wewaler” (prohibition), consist of sacred values and meanings in various contexts.